Superstitious thinking and its relationship with suggestibility in a students’ sample in Damascus University (Damascus University Journal of educational and Psychologyical sciences, 2025)
The research aims to investigate the degree of prevalence of superstitious thinking and suggestibility among members of the research sample, as well as to identify the relationship between superstitious thinking and susceptibility to sugestibility, and to reveal differences in superstitious thinking and susceptibility to suggestibility according to the variables of gender and academic year. To achieve these goals, the Superstitious Thinking Scale prepared by Al-Ahmad (2017), and the Suggestibility Scale prepared by Kotov, Bellman, and Watson (2004) and rationed by Al-Shorbagy and Al-Harbi (2016), were used. The research sample was (317) male and female students in the second and fifth years of dentistry and psychological counseling at the University of Damascus. The concluded results are:• he prevalence of superstitious thinking and suggestibility among members of the research sample was of a medium level.• There is a statistically significant relationship between superstitious thinking and suggestibility.• There are statistically significant differences between the averages of students’ performance on the two scales of superstitious thinking and suggestibility according to the gender variable, in favor of females.• There are statistically significant differences between the averages of students’ performance on the two scales of superstitious thinking and suggestibility, related to the academic year variable, in favor of the second students.
Keywords: Superstitious Thinking; Suggestibility